A Synchronization Approach Based on Bidirectional Correlation Search for Aperiodic Chaotic Direct Sequence Spread Spectrum Signals - Guogang Yuan; Zili Chen; Xijun Gao; Jiangyan He; Hongxia Jia (IEEE Access, 2020)
The chaotic direct sequence spread spectrum (CD3S) is one of the distinguished techniques providing physical layer secrecy and low probability of intercept (LPI) in wireless communication. Due to the noise-like and aperiodic characteristics of chaotic signals, the synchronization of CD3S signals is a challenging issue. A synchronization approach for aperiodic CD3S signals based on bidirectional correlation search (BDCS) is proposed. Through a joint acquisition of forward frequency domain matched filtering (FDMF) and backward FDMF, the synchronization module aligns received CD3S signals with local chaotic sequences without aid of the pilot signal. The probability distribution of correlator output is derived with additive white Gaussian noise and narrowband jamming. The probability of detection, probability of false alarm, and bit error rate are analyzed mathematically. An approximate solution of the local optimal acquisition threshold coefficient is obtained. These theoretical analyses are verified by numerical simulations, the results of which demonstrate that the proposed synchronization approach enables the CD3S system to resist interception and adapt to the environment with low signal-to-noise and signal-to-jammer ratios.